2010
DOI: 10.1111/j.1439-0434.2009.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Prepenetration Events Associated with the Infection of Common Bean by the Anamorph and Teleomorph ofGlomerella cingulataf.sp.phaseoli

Abstract: Glomerella cingulata f.sp. phaseoli and Colletotrichum lindemuthianum are the teleomorph and anamorph, respectively, of the pathogen causing anthracnose in common bean. The mechanisms relating to the sexual reproduction of this plant pathogen are still unclear, as are the infection structures involved and the symptoms produced. In the present study, bean plants were inoculated with ascospores and conidia, and the events taking place within the following 120 h were investigated using light microscopy and scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…The ability of the pathogen to rapidly overcome sources of host resistance is not well understood, but the frequent recovery of fertile Glomerella strains from anthracnose lesions suggested sexual recombination as one possibility. Previous studies have identified Glomerella strains recovered from anthracnose lesions as Glomerella lindemuthiana or Glomerella cingulata f.sp phaseoli , assuming them to be the teleomorphs of C. lindemuthianum [11], [13], [32], [34]. However, the results of the current study do not support the hypothesis that these Glomerella isolates are related to C. lindemuthianum .…”
Section: Discussioncontrasting
confidence: 95%
“…The ability of the pathogen to rapidly overcome sources of host resistance is not well understood, but the frequent recovery of fertile Glomerella strains from anthracnose lesions suggested sexual recombination as one possibility. Previous studies have identified Glomerella strains recovered from anthracnose lesions as Glomerella lindemuthiana or Glomerella cingulata f.sp phaseoli , assuming them to be the teleomorphs of C. lindemuthianum [11], [13], [32], [34]. However, the results of the current study do not support the hypothesis that these Glomerella isolates are related to C. lindemuthianum .…”
Section: Discussioncontrasting
confidence: 95%
“…Roca, unpublished). On the host leaf surface, C. lindemuthianum was found to grow and undergo CAT fusion for 48-72 h before there was any evidence of penetration into the leaf (Ishikawa et al 2009). (4) Conidia from older cultures of C. lindemuthianum (optimally 16-d-old cultures grown on bean pod agar) underwent the highest amount of CAT fusion.…”
Section: Discussionmentioning
confidence: 95%
“…CAT fusion has been previously observed on the surfaces of host leaves inoculated with Colletotrichum spp. (Latunde-Dada et al 1999;Ishikawa et al 2009). In a number of other ascomycete fungi, including plant pathogens, it has been previously found that conidial germling fusion can be increased when the rich organic growth medium is diluted (Laibach, 1928;Kö hler 1930;Glass & Fleißner 2006;Read et al 2010).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, absence of such symptoms in plants inoculated with G. cingulata f. sp phaseoli isolates has been reported (Camargo Jr. et al, 2007;Ishikawa et al, 2009); the symptoms in the sexual phase are milder than those presented during the asexual phase.…”
Section: Discussionmentioning
confidence: 92%